Literature Review: Penetapan Kadar Senyawa Aktif Antioksidan Pada Kulit Buah Alpukat - Ermi Abriyani; Frida Fatmawati; Jihan Khairunnisa; Aulia Rizqi Septiani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The avocado plant (Persea Americana Mill.) is a medicinal plant and belongs to the Lauraceae family which has many medicinal properties. Avocado skin contains flavonoid compounds that can be used to protect and reduce damage to the skin due to UV rays. The active substances contained in the avocado plant (Persea americana Mill.) are flavonoids and quercetin. In a sample used on quercetin as a standard solution from the peel for avocado. This study aims to determine the levels of flavonoids and active antioxidant compounds in the skin of avocado (Persea americana Mill.) using the UV- Vis spectrophotometry method. Determination of the levels of flavonoid compounds in the ethanol extract of avocado peel (Persea americana Mill.) was determined based on the absorbance value measured at a maximum wavelength of 435 nm using a quercetin ratio.